Empowering Batik Artisans in the Context of Modernization: A Case Study of Batik Gunawan Setiawan Industry - Alam, Logga Berlian Restu R (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: The batik industry is part of the creative economy sector that not only contributes to cultural preservation but also creates local economic opportunities. This study aims to analyze the empowerment strategies for batik artisans and examine the application of Rostow's modernization theory in the development of Batik Gunawan Setiawan Industry. Research Methods: This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. Finding/Results: The findings reveal that empowerment efforts include skills training, human resource development, performance-based incentives, and the use of digital platforms for marketing and promotion. Furthermore, the industry's growth aligns with the stages of Rostow's modernization theory, progressing from traditional practices to a modern, globally competitive enterprise. Conclusion: This study highlights that the integration of cultural preservation with modernization is essential for the sustainability of the batik industry in the global era.